Preclinical in vivo Neurotoxicity Studies of Drug Candidates - N. V. Eremina; L. G. Kolik; R. U. Ostrovskaya; A. D. Durnev (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Neurotoxic effects are one of the common reasons for discontinuation of preclinical and/or clinical studies. Preclinical evaluation of neurotoxic effects is complicated due to a wide range of manifestations and degrees of severity. Current experimental approaches to neurotoxicity assessment are cumbersome, laborious and not adapted enough for preclinical studies in the early stages of drug development. The aim of the study was to review existing approaches to experimental assessment of neurotoxic potential of new drugs and to discuss the need for and feasibility of developing and using integrated rapid neurotoxicity tests for early assessment of a pharmacological project’s potential. The authors reviewed scientific literature and guidance documents and analysed current approaches to chemical compound neurotoxicity assessment in laboratory animals. The paper analyses the main issues of neurotoxicity assessment for new drugs and compares Irwin tests with the functional observation battery. It analyses issues related to assessment of drugs’ effects on the development and maturation of central nervous system functions at pre- and postnatal stages. It was determined that the current practice is not sufficient for assessment of potential adverse effects on cognitive functions. The authors assessed factors affecting cognitive functions of rodents during studies. The “Acute suppression of the exploratory and orientation response” and “Extrapolation escape task” tests were proposed for validation as potential rapid tests for detection of an array of organic and functional neurotoxic disorders at early stages of preclinical studies.